Keanekaragaman Jenis Ikan di Ekosistem Padang Lamun Desa Kayubulan, Kecamatan Batudaa Pantai Kabupaten Gorontalo - Sitti Nursinar; Sri Fahriani Gusasi; Citra Panigoro (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the types of fish that have been identified, the value of species composition, diversity index, uniformity index, and dominance index in the seagrass ecosystem of Kayubulan Village, Batudaa Pantai District, Gorontalo Regency. This research was conducted from December 2021 to January 2022. This study was conducted with 4 sampling times consisting of 3 stations, each station consisting of 3 transects using drift gill net fishing gear with a net length of 17 m, a net height of 1 m, a mesh size of 2.5 inches, and also measuring seawater quality parameters which were carried out directly at the research site shortly before fish sampling. The results showed that 229 fish individuals consisting of 48 species and 21 families were found. Acanthurus auranticavus has the highest composition of 27.51%. The diversity index value (H') was 3.0203, indicating high diversity. The uniformity index (E) was 0.7802, indicating stable uniformity. Aquatic environmental conditions, such as temperature, pH, and salinity support the survival of fish in the area.